Analysis Of The Impact Of Health Services And Facilities On The Decline In Patient Visits At Sangkunur Community Health Center - Normayanti Rambe; Lisna Khairani Nasution; Susi Febriani Yusuf (PT Inovasi Pratama Internasional, 2026)
The use of Puskesmas as a center for basic health services in the community is still minimal. The results of the North Sumatra Provincial Susenas in 2021 where the population who treated the road was recorded at 17.47% in utilizing the Auxiliary Puskesmas / Puskesmas. The study aims to analyze the effect of health worker services, facilities, and infrastructure on the decrease in community patient visits (non-PBI) of the Sangkunur Health Center. The type of research used is analytical quantitative research with the Explanatory Research type, with a sample of all patients aged ≥ 17 years, who went to the Sangkunur Health Center, with a Non-PBI category of 243 people. The Statistical Test used is the chi-square test and linear logistic regression. The results showed that there was an influence of health services on the decrease in patient visits to the Sangkunur Health Center with a p-value = 0.000. The conclusion is that the poor service of health workers resulted in respondents decreasing visits at the Sangkunur Health Center.